PS-CSS particle swarm-based course scheduling system - Alcala, Mary Nhiza; Cayetano, Charmagne Ladannie; Mogarte, Christianne (2007)
The course scheduling problem has a large search space, is highly constrained, and requires an advanced solution representation which will then be evaluated over a set of fitness functions. This is a recurring but practical problem that every educational institution has to deal with. The previous CSS project proved that a multi-objective evolutionary approach is a good way to address the course scheduling problem, despite its complexity. Our project, PC-CSS, once again places this problem under a microscopic lens and proposes another web-based solution, employing Particle Swarm Optimization (PSO) - an algorithm which has not been applied in a large scale framework like university scheduling - as its underlying scheduling algorithm. We take a leap further as a multi-objective version of PSO is introduced, which will generate the set of nondominanted solutions for scheduling problem and is proven to work better in most functions as compared to other multi-objective algorithm of its type.
Thesis (B.S. Computer Science)--University of the Philippines, Diliman.
Keywords: Program transformation (Computer programming).; Particle swarm-based course scheduling system (PS-CSS).; Particle swarm optimization